Pre-Weaned Calf Rearing on Northern Irish Dairy Farms: Part 1. A Description of Calf Management and Housing Design - Aaron J Brown; Gillian Scoley; Niamh O’Connell; Jamie Robertson; Amanda Browne; Steven Morrison (Animals, 2021)
The first few months of life are of great importance to the longevity and lifetime performance of dairy cows. The nutrition, environment and healthcare management of heifer calves must be sufficient to minimise exposure to stress and disease and enable them to perform to their genetic potential. Lack of reporting of farm management practices in Northern Ireland (NI) makes it difficult to understand where issues impacting health, welfare and performance may occur in the rearing process. The objective of this study was to investigate housing design and management practices of calves on 66 dairy farms across NI over a 3-month period and also identify areas that may cause high risk of poor health and performance in dairy calves. An initial survey was used to detail housing and management practices, with two subsequent visits to each farm used to collect animal and housing-based measurements linked to hygiene management, animal health and performance. Large variations in key elements such as weaning criteria and method, calf grouping method used, nutritional feed plane, and routine hygiene management were identified. The specification of housing, in particular ventilation and stocking density, was highlighted as a potential limiting factor for calf health and performance. Lack of measurement of nutritional inputs, hygiene management practices and calf performance was observed. This poses a risk to farmers’ ability to ensure the effectiveness of key management strategies and recognise poor calf performance and health.